The Effect of Related Party Transactions on Audit Report Lag with Political Connections as a Moderating Variable - Hakim, Rhanisa Putri; Achmad, Komarudin (TEMA, 2025)
This study aims to examine the positive effect of Related Party Transactions (RPT) on Audit Report Lag (ARL) with political connections as the moderating variable. The population consists of non-cyclical sector companies, specifically, the food and beverage sub-sector listed on the Indonesian Stock Exchange (IDX) during the period of 2020-2022, from which 87 sample companies with a total of 132 observable secondary data of company annual reports are obtained. The results of the moderation regression analysis reveal that the RPT values in purchases and other liabilities have a negative effect on ARL. Furthermore, political connections negatively moderate the relationship between ARL and RPT in purchases, and positively moderate the relationship between ARL and RPT in purchases and receivables.